BLOGGING PHENOMENON: A NEW SOCIAL FORCE IN THE DIGITAL SOCIETY - Qurbanova, Nafisa (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
In recent years, the development of digital technologies and the growing popularity of social media have led to the emergence of blogging as a new form of social influence. Unlike traditional mass media, bloggers stand out for their rapid response to current issues, direct engagement with their audience, independent perspectives, and freedom of expression. This article examines the position, impact, and social relevance of the blogging phenomenon within a digital society. The relevance of the study lies in the fact that blogging in Uzbekistan is evolving independently from traditional journalism and is increasingly functioning as a tool for public oversight, civic engagement, and information exchange. The research poses the following central question: How is blogging emerging as a social force in the digital age, and what is its interaction with traditional media? The study employs content analysis, comparative analysis, and observational methods. It analyzes the activity of influential bloggers, their posts, and the extent of their impact on society. A survey was conducted among 182 active social media users. Results show that 88% of respondents primarily follow video bloggers, especially those focused on lifestyle and humor. The remaining 2 % follow bloggers who produce educational and popular science content. Content analysis also revealed that bloggers often raise social issues earlier than journalists, attract public attention, and in some cases, influence official decision-making. This article considers blogging not only as a communication tool but also as a potential emerging social institution.